Performance of Modified Alumina-Supported Ruthenium Catalysts in the Reforming of Methane with CO2 - Maina, Silvia Carolina Palmira (2023)
Ruthenium (1 wt%) catalysts supported on alumina doped with alkaline (Na and K) and alkaline earth metals (Ba, Ca, and Mg) of different concentrations (1, 5, and 10 wt%) were tested in the dry reforming of methane. All catalysts were prepared by the successive impregnation method. Supports were characterized by X-ray diffraction, BET surface area, temperature-programmed desorption of CO2, and 2-propanol dehydration. Additionally, catalysts were characterized by temperature-programmed reduction (TPR), temperature-programmed oxidation (TPO), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Stability tests to study coke deposition were performed using long-time dry reforming reactions. All the catalysts showed good catalytic activity, and activity falls were never detected. Ru metallic phase seemed to be resistant to coke formation even though its particles are sintered during a long-term reaction.